Brucine alleviates neuropathic pain in mice via reducing the current of the sodium channel. (6th April 2019) - Yu, Guang; Qian, Linnan; Yu, Juanjuan; Tang, Min; Wang, Changming; Zhou, Yuan; Geng, Xiao; Zhu, Chan; Yang, Yan; Pan, Yang; Shen, Xu; Tang, Zongxiang
Abstract: Ethnopharmacological relevance: Strychnos nux-vomica L. (Loganiaceae) is grown extensively in South Asian. The dried seed of this plant, nux vomica, has been clinically used in Chinese medicine for relieving rheumatic pain, reducing swelling and treating cancer. Brucine, the second abundant alkaloid constituent of nux vomica, shows excellent clinical therapeutic effect, especially in relieving pain, but mechanism of brucine in relieving pain is still unclear. Aim of the study: Explore the analgesic effect of brucine, reveal the molecular mechanism of brucine analgesia. Materials and methods: Antinociceptive effects of brucine were assessed in acute and chronic pain mice model. Electrophysiological experiments were used to evaluate the effects of brucine on neuronal activity and sodium channel function. Results: In acute pain models, brucine significantly inhibits response induced by nociceptive heat and mechanical stimulation. Furthermore, thermal hypersensitivity and mechanical allodynia were also alleviated by brucine treatment in a chronic constriction injury (CCI) mouse model. Sodium channel plays a crucial role in neuropathic pain. Electrophysiological results show that brucine inhibits the excitability of DRG neurons directly, the number of action potential (AP) was significantly reduced after brucine treatment, and this kind of inhibition is due to brucine inhibits both tetrodotoxin-sensitive (TTXs) and tetrodotoxin-resistant (TTXr) sodium channel. Conclusions: Taken together, brucine is a novel drug candidate in treating acute and chronic pain diseases, which might be attributed to inhibition the excitability of sodium channel directly. Graphical abstract: fx1